The Systematic Use of Corporate Social Responsibility by Small Companies - Šimonová, Stanislava; Vrabcová, Kristýna (EDP Sciences - Web of Conferences, 2021)
Research background: The responsibility of organizations towards their surroundings, society and the surrounding world is a long-term strategic goal, which is supported by various projects and concepts, at the national, European and global levels. The conception of sustainable development represents a model of society development, where economic and social development should be in line with the preservation of natural values for present and future generations. Purpose of the article: The concept of Corporate social responsibility (CSR) is a voluntary commitment of an organization that wants to behave responsibly towards its surroundings. The concept is generally understood as a strategic initiative that contributes to a brand's reputation and it is applied mainly by large companies. Small and medium-sized companies are rather not interested in the concept, on the one hand, its application is voluntary and on the other hand, they are afraid of the burden for the company (financial, organizational). The paper focuses on the potential of systematic use of the CSR concept by small organizations. Methods: The survey was conducted in selected small organizations. The degree of acquaintance with the principles of the concept and especially with the possibilities of the concept was determined, the current state was analyzed and activities for implementation were proposed, and indicators for long-term monitoring and evaluation were proposed. Findings & Value added: CSR concept encourages the company to make a positive impact on the environment and stakeholders. Small organizations often apply some of its principles, unknowingly by their natural responsible behavior. However, a systems-conscious approach is important. Small businesses can use the potential of the concept and implement its principles for the benefit of themselves and their surroundings.
Systematické využívání konceptu Společenské odpovědnosti podniků malými organizacemi
Keywords: corporate social responsibility; small and medium-sized companies; sustainable development; society development